Solution NMR backbone assignments of disordered Olduvai protein domain CON1 employing Hα-detected experiments - Paukovich, Natasia; Henen, Morkos A.; Hussain, Alya; Issaian, Aaron; Sikela, James M.; Hansen, Kirk C.; Vögeli, Beat (Biomolecular NMR assignments, 2022)
Olduvai protein domains, encoded by the NBPF gene family, are responsible for the largest increase in copy number of any protein-coding region in the human genome. This has spawned various genetics studies which have linked these domains to human brain development and divergence from our primate ancestors, as well as currently relevant cognitive diseases such as schizophrenia and autism spectrum disorder (ASD). There are six separate Olduvai domains which together form the majority of the various protein products of the NBPF genes. The six domains include three conserved domains (CON1-3), and three human-lineage-specific domains (HLS1-3) which occur in triplet. Here, we present the solution nuclear magnetic resonance backbone assignments for the CON1 domain, which has been linked to the severity of ASD. The data confirm that CON1 is an intrinsically disordered protein (IDP). Additionally, we use innovative H α -detected experiments which allow us to not only assign the H α atoms and N atoms of proline residues, but also to assign residues where H N -experiments suffered from peak overlap or broadening.